Techno-Economic Feasibility and Bibliometric Literature Review of Integrated Waste Processing Installations for Sustainable Plastic Waste Management - S. Samsuri; Saepul Anwar; Sri Harini; Tini Kartini; Nova Monaya; W. Warizal; Ade Budi Setiawan (ASEAN Journal for Science and Engineering in Materials, 2025)
This study presents a techno-economic analysis of the development of integrated waste processing installations, focusing on plastic waste management. The research evaluated a 20-year business feasibility using various financial indicators, including gross profit margin (GPM), internal rate of return (IRR), payback period (PBP), and net present value (NPV). Additionally, this study includes a literature review supported by bibliometric analysis to contextualize current trends in waste processing innovation and economic sustainability. The findings indicated that the project was technically viable and economically promising. The PBP analysis revealed that the investment became profitable after approximately three years, suggesting that the project met acceptable profitability benchmarks. The novelty of this research lies in its application of techno-economic analysis to assess both the technical feasibility and the economic value of waste management initiatives. Furthermore, this study contributes to the Sustainable Development Goals (SDGs), particularly by promoting responsible consumption and production (SDG 12) and fostering sustainable urban environments (SDG 11).